Factors influencing general practitioner choice among working-age population in Serbia - Knežević, Snežana; Dugalić, Anđelka; Đorđević, Slavica; Jandrić-Kočić, Marijana; Stajić, Dalibor (Medical Gazzette, 2026)
This study investigates how sick leave and socio-demographic and occupational factors affect the choice of general practitioners in Serbia. The objective was to identify the factors influencing the choice of a general practitioner among employees in Serbia, considering incidences of sick leave. The study analyzed data from the 2019 Serbian National Health Survey, including 4,652 participants aged 18 to 65 years, using descriptive statistics and binary logistic regression. Overall, 92.4% of participants, mostly employees in the public sector (85.2%), chose a general practitioner, with a higher prevalence among episodes of prolonged sick leave (92.8%). The choice of a general practitioner is influenced by socio-demographic and health-related factors. Being employed by an employer increases the likelihood of choosing a general practitioner (OR = 2.277), while blue-collar workers (OR = 0.757) and employees of middle and poor wealth status have a lower likelihood among participants without sick leave (middle OR = 0.709, poor OR = 0.701). Employees in Vojvodina with sick leave have a lower likelihood of choosing a general practitioner (OR = 0.111). The last visit to a general practitioner is a significant predictor for both groups. Socio-demographic, work-related factors, and health status significantly influence the choice of general practitioner among employees in Serbia, indicating the importance of accessible primary healthcare during periods of sick leave.